Measuring Values with Picture-Based Value Survey in Middle Childhood: Changes in terms of Age, Sex and Mother’s Education - Zeynep ÇAKMAK; Ayşe Vildan ACAR-BAYRAKTAR; Dilek SARITAŞ-ATALAR (Nesne Psikoloji Dergisi, 2018)
Acquisition of values in childhood has become an attention-grabbing topic in recent years. The aim of this study was to apply the Picture-Based Value Survey (PBVS-C) to children whose ages ranged from 6 to 11 years and to examine value priorities in middle childhood, value changes related to age, sex, and mother’s education. For this aim, PBVS-C was applied to 192 students from 1st, 2nd, 3rd, and 4th grades who resided in Ankara and whose ages ranged from 6 to 11 years in Ankara (49 % girls, Sgirl = 1.17; 50.5 % boys, Sboy = 1.25). Multidimensional scaling analysis was used to confirm the circular structure of values proposed by Schwartz and the PROXSCAL module in the SPSS program was used for statistical calculations. The value sequence obtained from multidimensional scaling analysis showed a very similar distribution to the value sequence proposed by Schwartz. Accordingly, Schwartz's theoretical model has been confirmed, in accordance with the four-dimensional structure consisting of two bipolar dimensions: openness-to-change - conservation and self-enhancement -self-transcendence. Moreover, it was found that children give priority to values of benevolence, universality, and security, and higher-order values of self-transcendence and selfenhancement. Our research findings showed that value priorities differ according to age, sex, and mother’s education. Therefore, these findings can be a guide for professionals working in and out of the schools.